Nutritional and water needs - Sanchez, J.; Mata, F.; Grimaldi, M.; Dominguez, R. (Coaching and Sport Science Review, 2017)
Tennis is a sport with high liquid and nutrition requirements. A correct nutritional - dietetic approach assures health as well as an optimal performance for the tennis player. All approaches must be based on the determination of those factors that reduce sport performance, in order to set a number of targets based on those factors, and then set the most appropriate strategies to achieve the targets proposed.